Accountability in acute in-patient mental healthcare: advancing structural and cultural change - Corrado Barbui; Charlene Sunkel; Graham Thornicroft (The British Journal of Psychiatry, 2026)
Summary Following safety failures and gaps in oversight, acute in-patient mental health services face increasing scrutiny. This article examines accountability, conceptualised as answerability, responsibility and responsiveness, and reviews key strategies. Evidence varies in strength, with strongest support for reducing coercion and measurement systems. Structural and cultural alignment is essential for sustained improvement.